Progress in the cryoablation and cryoimmunotherapy for tumor - Chen, Zenan; Meng, Liangliang; Zhang, Jing; Zhang, Xiao (Frontiers in Immunology, 2023)
With the rapid advancement of imaging equipment and minimally invasive technology, cryoablation technology is being used more frequently in minimally invasive treatment of tumors, primarily for patients with early tumors who voluntarily consent to ablation as well as those with advanced tumors that cannot be surgically removed or cannot be tolerated. Cryoablation is more effective and secure for target lesions than other thermal ablation methods like microwave and radiofrequency ablation (RFA). The study also discovered that cryoablation, in addition to causing tumor tissue necrosis and apoptosis, can facilitate the release of tumor-derived autoantigens into the bloodstream and activate the host immune system to elicit beneficial anti-tumor immunological responses against primary. This may result in regression of the primary tumor and distant metastasis. The additional effect called “ Accompanying effects “. It is the basis of combined ablation and immunotherapy for tumor. At present, there is a lot of research on the mechanism of immune response induced by cryoablation. Trying to solve the question: how positively induce immune response. In this review, we focus on: 1. the immune effects induced by cryoablation. 2. the effect and mechanism of tumor immunotherapy combined with cryoablation. 3.The clinical research of this combination therapy in the treatment of tumors.